A one-way terahertz plasmonic waveguide based on surface magneto plasmons in a metal-dielectric-semiconductor structure - Hu, Bin (2013)
A novel one-way-propagating terahertz plasmonic waveguide at a subwavelength scale is proposed based on a metal-dielectric-semiconductor structure. Unlike one-way plasmonic devices based on interference effects of surface plasmons, the proposed one-way device is based on nonreciprocal surface magneto plasmons under an external magnetic field. Theoretical and simulation results demonstrate that the waveguide has a broadly tunable one-way-propagating frequency band by the external magnetic fields. The proposed one-way device can be used to realize various high performance tunable plasmonic devices such as isolators, switches and splitters for ultracompact integrated plasmonic circuits.